Effect of plant age, leaf age and leaf position on infection of carrot leaves by Cercospora carotae - Van Delden, A.; Carisse, O. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1993)
A greenhouse study was conducted to determine the effects of plant age, leaf age and leaf position on infection of carrot (Daucus carota var. sativa) by Cercospora carotae. Infection was quantified as the number of lesions cm-2 of leaf surface and the length of incubation period. The relative number of lesions decreased linearly with increasing plant age from 39- to 60-d-old plants, and remained low from 60- to 71-d-old plants. The incubation period increased from 9.0 to 16.6 d, with increasing plant age. Relative number of lesions decreased with increasing leaf age from 1 to 36 d, but the variation among leaves was high. The incubation period increased from 9.0 to 18.3 d with increasing leaf age, but lesions on a few young leaves appeared relatively late. Generally, differences in relative number of lesions for leaves on different positions for 10- and 13-wk-old plants were not significant. Infection on all leaves except the two youngest was representative of infection on whole plant. Effect of leaf position on incubation period was different for the 10- and 13-wk-old plants and for the two trials. Plants younger than 60 d old, in the seven-to eight-leaf stages should be used for experiments on the initial development of Cercospora blight of carrots.